2012
DOI: 10.1097/sle.0b013e31824eda3c
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Transperitoneal Partial Nephrectomy for Renal Hydatid Cyst

Abstract: A 29-year-old female patient with an isolated hydatid cyst in the lower pole of the left kidney presented with a history of weight loss and cloudy, foul-smelling urine. Laparoscopic partial nephrectomy was performed, at which the cyst was removed en bloc. On the fifth postoperative day, she was discharged without any complication. Nine months postoperatively, a computed tomography scan revealed no recurrence of hydatidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, minimal invasive NSS was also reported that depended on the size and location of the renal hydatid mass lesion. 15 Following surgical resection, excellent outcomes have been reported with complete or partial surgical resection, with most patients having no recurrences. 6,10…”
Section: Discussionmentioning
confidence: 99%
“…However, minimal invasive NSS was also reported that depended on the size and location of the renal hydatid mass lesion. 15 Following surgical resection, excellent outcomes have been reported with complete or partial surgical resection, with most patients having no recurrences. 6,10…”
Section: Discussionmentioning
confidence: 99%
“…Ideally if one can use a serological test to diagnose hydatid disease that would tend to be very helpful. Krige and Beckingham [35] iterated the ensuing:…”
mentioning
confidence: 99%